HIV/AIDS Related Stigma and Discrimination against PLWHA in Nigerian Population - Dahlui, M.; Azahar, N.; Bulgiba, A.; Zaki, R.; Oche, O.M.; Adekunjo, F.O.; Chinna, K. (Public Library of Science, 2015)
Background HIV/AIDS remain a major public health concern in Nigeria. People living with HIV/AIDS (PLWHA) face not only personal medical problems but also social problems associated with the disease such as stigma and discriminatory attitudes. This study provides an insight into HIV/AIDS related stigma and discrimination against PLWHA in Nigeria. Methods The data for this study was extracted from the 2013 Nigeria Demographic and Health Survey conducted by the National Population Commission. All men and women aged 15-49 years, permanent residents and visitors of the households were eligible for the interview. Several questionnaires were used in the survey, some covering questions on HIV/AIDS. Results A total of 56 307 men and women aged 15-49 years participated in this national survey. About half of the population in Nigeria have HIV stigma. Younger persons, men, those without formal education and those within poor wealth index are more likely to have stigma towards PLWHA. In addition, married people are more likely to have stigma on PLWHA and are more likely to blame PLWHA for bringing the disease to the community. Also about half of the population discriminates against PLWHA. However, those with higher levels of education and those from higher wealth index seem to be more compassionate towards PLWHA. About 70% in the population are willing to care for relative with AIDS, even more so among those with higher level of education. Conclusion There is a high level of HIV stigma and discrimination against PLWHA in the Nigerian population. Education seems to play a major role in the society with respect to HIV stigma and discrimination against PLWHA. Educating the population with factual information on HIV/AIDS is needed to reduce stigma and discrimination towards PLWHA in the community.